Wpływ lokalizacji na konkurencyjność gospodarstw rolnych na przykładzie producentów sektora ogrodniczego Lubelszczyzny - Krukowski, Artur (Impact of Location on Farms' Competitiveness on the Basis of Horticultural Sector Producers from Lublin Region, 2006)
An article presents the conception of clusters - what these kinds of systems are how they perform and what the conditions and the economic effects of clusters development are. On the basis of horticultural sector an author makes an initial assessment of cluster development' potential by identifying a considerable concentration of horticultural production in a particular communes of Lublin voivodship. The results of research shows that in Lublin region there is a potential for creating and improving of the clusters' structures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 497-502